+0  
 
-1
122
4
avatar

The complex number z satisfies z^2 + z + 1 = 0.  Find \(z^2 + z\)

 May 20, 2022
 #1
avatar+310 
0

z^2 + z = ((-1+-isqrt(3)))^2/4 + (-1+-isqrt(3))/2 Then just add them up by multiplying the right one by 2/2

 May 20, 2022
 #2
avatar+9461 
0

Just move the 1 to the right-hand side and it's done.

 

\(z^2 + z + 1 = 0\\ (z^2 + z + 1) - 1 = 0 -1\\ z^2 + z = -1\)

 May 20, 2022
 #3
avatar+310 
0

Lol I'm the dumbest human of all time

hipie  May 20, 2022
 #4
avatar+9461 
+2

No, please don't say that. Sometimes we miss the most obvious things. I think you will not miss it next time, so that is progress!

MaxWong  May 20, 2022

17 Online Users